Makna Simbolik dalam Tradisi Adat Khatam Al-Qur’an Pada Acara Pernikahan Oleh Masyarakat Desa Sekernan Muaro Jambi - Aisi Nurmala Sari (Kuras Institute, 2024)
Every Muslim has various forms of interaction with the Qur'an. For example, the people of Sekernan Village make the recitation of khataman al-Qur'an part of the traditional wedding procession. In practice, this tradition has a unique procession that acculturates with local culture. Therefore, the community makes this tradition a religious ritual in the form of meaningful symbols that are believed to have a positive influence on the sustainability of building a household. So, this research aims to look at the procession and the meaning behind the practice. Using Clifford Geertz's theory, it is used as an analysis to find the meaning behind the symbols in the traditional tradition of khatam al-Qur'an. The results of this study show that there are several series of customs that must be carried out by the bride before reading the Qur'an. Among them are the procession of processions, weighing, then reading the khatam al-Qur'an starting from surah al-Duha to surah an-Nas accompanied by the Koran teacher and his parents. In addition, this tradition also has symbols that relate to the concept of religion, namely in the form of religious education, birrul walidain, and privileges that are believed to have ultimate meaning, so that it continues to be maintained to this day.